Challenges in Pancreatic Pathology - Seicean, Andrada (IntechOpen, 2017)
The assessment of the pancreas is a challenging problem because it has a profound location and it often presents difficulties in diagnosis and treatment. Despite many efforts in dealing with pancreatic diseases, the pathogenesis is not completely understood, the symptoms and imaging methods are unspecific, and the treatment possibilities are sometimes very limited. The major purpose of this book is to offer the reader a better understanding of the challenging aspects in pancreatic pathology, starting with anatomy and following with different pancreatic pathology. More space is allotted to pancreatic cancer, including surgical procedures, and to the management of the cystic lesions of the pancreas. This book is meant to provide a thorough guide for the best approaches in some of the difficult problems in pancreatology.